KONDISI SANITASI RUANG TAHANAN 01 lEMBAGA PEMASYARAKATANKELAS II A PAMEKASAN - Farhatul Latifah; Umi Rahayu; Siti Surasri (GEMA LINGKUNGAN KESEHATAN, 2015)
Sanitary condition of detention cells in the correctional institution (prison) class II A of PamekasanDistrict wasnot in accordance with health requirements. This was reflected by the condition of the basic sanitary facilities.The purpose of this research was to identify the sanitary state of the detention cells in the correctionalinstitution class II A of PamekasanDistrict.This was a descriptive study using cross sectional design and it was also a field research. Data were collectedthrough observations, interviews, measurements, and laboratory tests.The result showed that the detention cells scored 197 (80%) out of a total score of 245, meaninh that theydid not met the health requirements. Several variables considered that did not satisfy the health requirementsincluded water supply, sewage disposal, and "eradtcatlon of insects. The hygienic behavior of the inmatesscored 64-68%, meaning it did not satisfy the health requirements. It can be concluded that sanitarycondition of the detention cells did satisfy the designated health requirements. The administrators of thecorrectional institution in Pamekasan need to improve condition of the sanitary facilities up to the standarddesignated in the sanitary guidelines for public places of the Ministry of Health in 1984. Inmates and otherpeople who live in the correctional institution should keep up the condition of sanitary facilities, use themproperly and enhance their hygienic behavior in the correctional institution.